Modelling the birth and death of cartels with an application to evaluating antitrust policy - Joseph E. Harrington (Jr.) (The Johns Hopkins University, Department of Economics, 2006)
One of the primary challenges to measuring the impact of antitrust policy on collusion is that the cartel population is unobservable; we observe only the population of discovered cartels. To address this challenge, a model of cartel creation and dissolution is developed to endogenously derive the populations of cartels and discovered cartels. It is then shown how one can infer the impact of antitrust policy on the population of cartels by measuring its impact on the population of discovered cartels. In particular, the change in the distribution on the duration of discovered cartels could be informative in assessing whether a new antitrust policy is reducing the latent rate of cartels.
Keywords: 330